Adaptive Cardiac Metabolism Under Chronic Hypoxia: Mechanism and Clinical Implications - Su, Zhanhao; Liu, Yiwei; Zhang, Hao (Frontiers in Cell and Developmental Biology, 2021)
Chronic hypoxia is an essential component in many cardiac diseases. The heart consumes a substantial amount of energy and it is important to maintain the balance of energy supply and demand when oxygen is limited. Previous studies showed that the heart switches from fatty acid to glucose to maintain metabolic efficiency in the adaptation to chronic hypoxia. However, the underlying mechanism of this adaptive cardiac metabolism remains to be fully characterized. Moreover, how the altered cardiac metabolism affects the heart function in patients with chronic hypoxia has not been discussed in the current literature. In this review, we summarized new findings from animal and human studies to illustrate the mechanism underlying the adaptive cardiac metabolism under chronic hypoxia. Clinical focus is given to certain patients that are subject to the impact of chronic hypoxia, and potential treatment strategies that modulate cardiac metabolism and may improve the heart function in these patients are also summarized.